Keberadaan Permukiman Kumuh Tambak Lorok Kota Semarang terhadap Pengembangan Kampung Wisata Bahari - Ajeng Pradita Dewi; Sunarti Sunarti (Teknik PWK (Perencanaan Wilayah Kota), 2019)
Slum areas are found in some coastal areas, one of them in Semarang, Desa Tanjung Mas, Tambak Lorok. Semarang city slum ± 415.83 Ha set out in the Decree of Mayor of Semarang No.050 / 801/2014. On the other hand the government will develop a marine tourism village in its territory. In the development of marine tourism village there is one of the criteria that must be fulfilled is a clean environment, beautiful, and adequate facilities and infrastructure. The method used in this research is quantitative. The analysis shows that Tambak Lorok has got slum repair program. Despite getting the arrangement program, until now Tambak Lorok still slum because many aspects that have not been handled. The condition of the settlement is still unfit and unhealthy. Given the government's plan for a marine tourism village development program in Tambak Lorok, the existence of settlements is currently not ready to support the plan. The settlement of Tambak Lorok, which is the destination of marine tourism, still needs improvement from various aspects, such as residential, road, drainage, garbage, sanitation, drinking water, and also trade facilities. With the improvements in these aspects, Tambak Lorok will have improved the quality of settlements to support the marine tourism village.